The Comparison of Pitch Between Ethiopian and Somalian in English Sentences - Krisna Weny; Tengku Syarfina; Mutiara Zein; Rahmadsyah Rangkuti (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This study examines pitch variations in English sentences spoken by two non-native children from Ethiopia and Somalia, using. The research focuses on declarative, imperative, and interrogative sentence types, analyzing pitch frequency across these sentence forms. The participants were a 5-year-old Ethiopian boy and a 9-year-old Somalian boy, were recorded, and their pitch data were analyzed for beginning, highest, lowest, and final frequencies. The results indicate that the Somalian boy exhibited greater pitch variation, particularly in declarative sentences, while the Ethiopian boy demonstrated more consistency. In imperative sentences, the Ethiopian boy showed slightly wider variation, while in interrogative sentences, the Somalian boy ended with a higher pitch. The differences in pitch usage suggest influences from age, language background, and individual speaking habits. This research contributes to understanding pitch use in young multilingual English learners and their linguistic development.